Dhanyang dan Prewangan: Kuasa Roh Halus dalam Dunia Mistik Orang Jawa Perantau di Dataran Tinggi Gayo - Shadiqin, Sehat Ihsan; Fuadi, Tuti Marjan (Sociology Department Of Syiah Kuala University, 2023)
The purpose of this study is to investigate how members of disadvantaged communities imagine